Langerhans cell histiocytosis; an institutional study (Journal of Pathology of Nepal, 2017)
Background: Langerhans cell histiocytosis is a complex rare disease of the dendritic cell system.The disease can occur at any age, with a peak at 5-10 years. Here, we present the spectrum of this uncommon disease with different sites of involvement and its histopathological differential diagnosis. Material and Methods:  Study included 24 cases of Langerhans cell histiocytosis out of approximately 50,000 biopsies received in the department.Results: The male to female ratio was 1.6:1 with mean age of 12 years. Commonest site of involvement was skin 37.5%, followed by bone 33.4%. Lymph nodes 20.9%, bone marrow 4.1% and thyroid 4.1% involvement was seen. Among the 9 cases of bone involvement, commonest site was humerus (3 cases), sternum (2 cases) and one case each in frontal bone, fibula, temporal bone and rib.Conclusion: Langerhans cell histiocytosis should be considered in the differential diagnosis of histiocytic lesions involving various organs, especially in childhood.